"I didn't want to be a troublemaker" – doctoral students' experiences of change in supervisory arrangements. (4th October 2021) - Schmidt, Manuela; Hansson, Erika
Abstract : Purpose: During the lengthy process of PhD studies, supervisory changes commonly occur for several different reasons, but their most frequent trigger is a poor supervisory relationship. Even though a change in supervisors is a formal bureaucratic process and not least the students' rights, in practice it can be experienced as challenging. Therefore, the purpose of this study is to explore how doctoral students experience a change in supervisory arrangements. Design/methodology/approach: This study highlights the voices of 19 doctoral students who experienced at least one supervisory change during their doctoral studies. Findings: The findings were structured chronologically, revealing the students' experiences prior, during and after the changes. In total, 12 main themes were identified. Most of the interviewed students experienced the long decision-making processes as stressful, difficult and exhausting, sometimes causing a lack of mental well-being. However, once the change was complete, they felt renewed, energized and capable of continuing with their studies. It was common to go through more than one change in supervisory arrangements. Further, the students described both the advantages of making a change yet also the long-lasting consequences of this change that could affect them long after they had completed their PhD programs. Originality/value: The study fulfills an identified need to investigate the understudied perspective of doctoral students in the context of change in supervisory arrangements. A change in the academic culture is needed to make any changes in supervisory arrangements more acceptable thus making PhD studies more sustainable.